2020
DOI: 10.1038/s41467-020-14688-0
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiration depletes groundwater under warming over the contiguous United States

Abstract: A warmer climate increases evaporative demand. However, response to warming depends on water availability. Existing earth system models represent soil moisture but simplify groundwater connections, a primary control on soil moisture. Here we apply an integrated surface-groundwater hydrologic model to evaluate the sensitivity of shallow groundwater to warming across the majority of the US. We show that as warming shifts the balance between water supply and demand, shallow groundwater storage can buffer plant wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
118
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 228 publications
(128 citation statements)
references
References 39 publications
8
118
0
2
Order By: Relevance
“…The role of lateral groundwater flow in watershed dynamics has been demonstrated in prior studies (e.g., Sear et al ; Brouyère et al ; Kollet and Maxwell ; Decharme et al ; Flessa et al ; Miller et al ; Fang and Pomeroy 2016; Buto et al ). On a large‐scale, Condon and Maxwell () and Condon et al () demonstrated the close connections between lateral groundwater flow streamflow and evapotranspiration (ET) using an integrated groundwater surface water model. However, few have investigated the role of lateral groundwater flow specifically in mountain headwater domains.…”
Section: Introductionmentioning
confidence: 99%
“…The role of lateral groundwater flow in watershed dynamics has been demonstrated in prior studies (e.g., Sear et al ; Brouyère et al ; Kollet and Maxwell ; Decharme et al ; Flessa et al ; Miller et al ; Fang and Pomeroy 2016; Buto et al ). On a large‐scale, Condon and Maxwell () and Condon et al () demonstrated the close connections between lateral groundwater flow streamflow and evapotranspiration (ET) using an integrated groundwater surface water model. However, few have investigated the role of lateral groundwater flow specifically in mountain headwater domains.…”
Section: Introductionmentioning
confidence: 99%
“…The need to incorporate local to regional scale subsurface processes into hydrological modeling has become increasingly evident across landscapes (e.g., Condon et al, 2020; Gleeson et al, 2011; Jefferson et al, 2010; O'Sullivan, Linnansaari, et al, 2019; Schaller & Fan, 2009). The inclusion of metrics that capture subsurface processes in spatial statistical models may overcome complexities that appear to be arising from variable groundwater and topography relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Reliable estimates of subsurface travel time could inform plans regarding legacy contaminants, set reasonable expectations for the length of the legacy (Meals et al, 2010), or suggest areas that are vulnerable to legacies. Reasonable predictions of flow path depth would be useful for contaminant remediation and plume characterization, for understanding geochemical reactions, as reaction environments typically vary by depth, in assessing vulnerability of groundwater discharge‐based cold water habitat to climate change, and in understanding the vulnerability of surface water flows to anthropogenic influences like groundwater pumping and climate change (Barnes et al, 2018; Benz et al, 2017; Briggs et al, 2018; Condon et al, 2020; Kolbe et al, 2019).…”
Section: Discussionmentioning
confidence: 99%